Cesarean scar pregnancy treated by curettage and aspiration guided by laparoscopy - Shu S; Luo X; Wang Z; Yao Y (Dove Medical Press, 2015)
Shan-rong Shu, Xin Luo, Zhi-xin Wang, Yu-hong Yao Department of Obstetrics and Gynecology, The First Affiliated Hospital of JiNan University, HuangPu Road West, Guangzhou, People’s Republic of China Abstract: Pregnancy in a cesarean scar is the rarest form of an ectopic pregnancy. The treatment for cesarean scar pregnancy mainly includes systemic methotrexate and uterine artery embolization. Here, we reported a case of cesarean scar pregnancy treated by curettage and aspiration guided by laparoscopy. The treatment plan included two phases. Three days after a combination of methotrexate and mifepristone was administered, the gestational sac was removed under laparoscopy, which enabled a successful treatment for the unruptured ectopic pregnancy in a previous cesarean scar and made it possible to preserve the reproductive capability of the patient. Keywords: cesarean scar pregnancy, laparoscopy, curettage and aspiration